Hydrogeological characterization of crystalline aquifer in the Hout River Catchment, Limpopo Province, South Africa - Abiye, T. A.; Tshipala, D.; Leketa, K.; Villholth, Karen G.; Ebrahim, Girma Yimer; Magombeyi, Manuel Simba; Butler, M. (Elsevier, 2020)
This study attempted to conceptualize the hydrogeological setting of the Hout River Catchment, located in the Limpopo River Basin, using multiple methods that include groundwater flow patterns, structural analysis, stable (18O, 2H and 13C) and radiogenic (14C) isotopes of water and Water Table Fluctuation methods. The hydrogeological system of the catchment is represented by fractured crystalline basement aquifer as the main host for groundwater and is overlain by weathered rocks that act as a vadose zone and shallow aquifer in various places. Groundwater from the fractured basement rocks is the main source of water for large-scale irrigation and domestic use. Potential aquifers in the area are evident within the Hout River granitic gneiss and the Goudplaats granitic gneiss besides the younger granites as a result of fracturing and weathering. Groundwater flow map shows a flow pattern from the southern part of the catchment towards the north-eastern part of the catchment dictated by dolerite dykes and tectonic lineaments that trend in the ENE and E direction (088° and 075°) with the dip angle of 50° to 55°. The deeper aquifer in the southern and central part of the catchment contain old groundwater with high salinity due to long residence time. The stable isotopes further confirmed the limited possibility of local recharge, with rather dominance of regional groundwater circulation into the catchment. The northern part of the catchment seems to be receiving recent recharge with the groundwater of high 14C content derived from the mountains that border the catchment.